Public libraries in Croatia and digitization challenge - Vrana, Radovan (Array, 2010)
The Internet has taken over the role of the main information provider among library users, especially among younger generations, changing their perspective and attitude towards libraries greatly, and increasing their inclination towards search engines instead of library resources. As a consequence, public libraries need to re-think their role in society and offer new material and services supported by digital technologies. Libraries already responded to this challenge by changing their acquisition policies to include digital information resources and by initiating digitization projects. Public libraries in Croatia are also changing under the pressure of the Internet and its users. In addition to acquisition of digitally born material, they have initiated digitization projects. Despite problems that they have encountered during realization of these projects, they recognize the importance of digital collections for promotion of their holdings and services and continue with digitization of the existing library material.